2016
DOI: 10.1016/j.bmc.2016.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of small molecule-sulfotyrosine mimetics that inhibit HIV-1 entry

Abstract: In the absence of a cure or vaccine for HIV/AIDS, small molecule inhibitors remain an attractive choice for antiviral therapeutics. Recent structural and functional studies of the HIV-1 surface envelope glycoprotein gp120 have revealed sites of vulnerability that can be targeted by small molecule and peptide inhibitors, thereby inhibiting HIV-1 infection. Here we describe a series of small molecule entry inhibitors that were designed to mimic the sulfated N-terminal peptide of the HIV-1 coreceptor CCR5. From a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The disulfonic acids were the most potent compounds. Surface plasmon resonance tests showed that these compounds bind to trimeric gp120 and docking studies also verified the structure–activity relationship results …”
Section: Hiv‐1 Entry Inhibitorsmentioning
confidence: 61%
See 2 more Smart Citations
“…The disulfonic acids were the most potent compounds. Surface plasmon resonance tests showed that these compounds bind to trimeric gp120 and docking studies also verified the structure–activity relationship results …”
Section: Hiv‐1 Entry Inhibitorsmentioning
confidence: 61%
“…Surface plasmon resonance tests showed that these compounds bind to trimeric gp120 and docking studies also verified the structure-activity relationship results. [31] Curreli et al in a continuous work reported two potent compounds, NBD-14088 and NBD-14107 (7 and 8, respectively; Figure 5), as CD4 mimic entry inhibitors that target the Phe43 cavity of HIV gp120. These compounds had better anti-HIV-1 effects and ADMET (absorption, distribution, metabolism, excretion, and toxicity) properties than the potent HIV-1 attachment inhibitor Temsavir 9 (BMS-626529; Figure 5).…”
Section: Ccr5 and Cxcr4 Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, peptide mimetics or smallmolecule inhibitors have been developed to block viral entry or to suppress viral infection, and similar strategies can also be applied to COVID-19. 142 Particularly, targeted immunotherapy using smallmolecule inhibitors to prevent cytokine storm syndrome has emerged as a potent treatment option for COVID-19 patients. 143 The ultimate objective of targeted immunotherapy is to optimize the cytokine productions and inflammatory responses upon viral infections.…”
Section: Perspectives: Treatment and Preventionmentioning
confidence: 99%